Study of Nonlinear Functional Differential Equations in Branch Algebras: Analysis and Applications of Nonlinear Functional Differential Equations in Physical and Biological Systems (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Presently the theory of nonlinear functional differential equation is a very active area of mathematical research and applications of theory are of fundamental importance in the formulation and analysis of various classes of operator’s equation which arise in the physical, biological, engineering and technological sciences. Usually the mathematical models or the equations that have been used to describe a particular phenomenon or process of the universe contain a certain parameter, which has some specific physical interpretation, but whose value is not known. If any such phenomena involving so mentioned parameter and which satisfy certain probabilistic or measure theoretic behavior with respect to the parameter, then we say it is a random phenomenon.